(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses appositional constructions in the German language. It explores the identification of appositional relations based on lexical-semantic factors, as well as the relationship between the appositional element and the main expression. Additionally, the views of several linguists on the connectors used in appositional elements, their structural characteristics, and their application are also presented.